Cold-inducible ribonucleic acid-binding protein attenuates acute kidney injuries after deep hypothermic circulatory arrest in rats. (14th August 2017) - Yu, Lei; Gu, Tianxiang; Liu, Yu; Jiang, Xuan; Shi, Enyi
Abstract: OBJECTIVES: Cold-inducible ribonucleic acid-binding protein (CIRP) has been identified to play a role in the antiapoptotic effect of hypothermia. We sought to investigate the renoprotection of CIRP in a rat model of deep hypothermic circulatory arrest. METHODS: Overexpression and knockdown of CIRP were achieved in vivo by directly injecting lentivirus vectors containing packaging lentivirus (pL)/internal ribosome entry site (IRES)/green fluorescent protein (GFP)-CIRP or pL/short hairpin RNA (shRNA)/F-cold inducible RNA binding protein (F-CIRP)-A into the renal parenchyma of rats 7 days before deep hypothermic circulatory arrest under the ultrasound guidance. The vehicles or control lentivirus vectors were given to the control group or the control vector group, respectively. Renal function and apoptosis activity were evaluated by serum cystatin C, serum/tissue neutrophil gelatinase-associated lipocalin and terminal deoxynucleotidyl transferase 2ʹ-deoxyuridine, 5ʹ-triphosphate nick-end labelling assay at 24 h after surgery. The expression of CIRP messenger RNA (mRNA) was assessed by quantitative real-time polymerase chain reaction. Protein expression of CIRP and caspase 3 was tested by Western blot. RESULTS: Compared with the sham group, rats in the control group showed increased expression of CIRP mRNA, CIRP protein, caspase 3 and the apoptotic rate ( P < 0.01). However, when compared with the control group, rats in the pL/IRES/GFP-CIRP group showed significantly decreased caspase 3 and apoptosis activities while further increased expression of CIRP mRNA and protein. Rats in the pL/shRNA/F-CIRP-A group showed increased caspase 3 and apoptosis activities and further decreased expression of CIRP mRNA and protein ( P < 0.01), when compared with the control group. Renal function was markedly protected in the pL/IRES/GFP-CIRP group and impaired in the pL/shRNA/F-CIRP-A group. CONCLUSIONS: Our findings suggest that the CIRP exerts a robust renoprotective effect by inhibiting apoptosis in the rat model of deep hypothermic circulatory arrest.